FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN MP-ASI SECARA DINI DI KELURAHAN BAGAN JAWA PESISIR WILAYAH KERJA PUSKESMAS BAGAN SIAPIAPI KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Endang Mayasari (Jurnal Doppler, 2018)
Women's reluctance to perform IVA tests is due to a lack of knowledge as well as feel embarrassed, anxious and fearful of the results of their examination stating they have cervical cancer. In the case from year to year cases of cervical cancer has been found in advanced stages, with the IVA test makes it easier for women to find cervical cancer as early as possible, because the IVA test is one of the early detection of cervical cancer with a simple method. The advantages of IVA test that is safe, accurate, does not take long on the results of examination and the cost is relatively cheap compared to other examinations. In Puskesmas Rawat Inap Simpang Tiga in 2015, women who do IVA test that is as many as 110 people with the result 102 declared negativ and 8 positive people. This research is analytical research with cross sectional approach. The population of this research were all women of reproductive age who were married in Rawat Inap Simpang Tiga Public Health Center that was 693 people with accidental sampling technique with a large sample of 40 people. The result of statistical test stated that there is a significant relationship between knowledge, attitude and support of husband with the implementation of IVA test with p value (0,027, 0,012 and 0,012). Suggestion of researcher to health officer to develop effective communication and information about the importance of early detection of cervical cancer with IVA method, and the formation of cancer cadres every posyandu in an effort to increase woman awareness for early detection of cervical cancer